“I Gave Up Football and I Had No Intention of Ever Going Back”: Retrospective Experiences of Victims of Bullying in Youth Sport - Ríos, Xènia; Ventura, Carles; Mateu, Pau (Frontiers in Psychology, 2022)
Bullying is a global issue that, beyond school, is present in different social contexts, such as sport environments. The main objective of this study was to get to know the experiences of victims of bullying in sport throughout their youth sport training. Semi-structured interviews to four Spanish women and seven Spanish men were carried out, within an age range of 17 to 27 (Mage = 21 years, SD = 3.69). The following main themes were established by means of a hierarchical content analysis: (a) “bullying characterization”, (b) “dealing with bullying”, and (c) “consequences of bullying”. The results show the presence of physical, verbal and social bullying in the sport context, with the changing room being the space where this type of behaviour is most frequently developed. Most victims show an internal attribution (self-blame) for the bullying event, related to their motor skills and their personal physical and psychological characteristics. Double victimization can be observed, at the sport club and at the educational centre. Passive strategies are used to deal with the situation, while little support is shown by sport agents (teammates and coaches). The victims, as a consequence of the bullying experience, suffer from short and long-term negative effects on a psychosocial level. The study highlights the necessity to design and implement programs focused on the prevention, detection and intervention of bullying for sport organisations, bearing in mind all the agents that make them up (coaches, management teams, families and players). Furthermore, the importance of promoting the creation of safe sport environments, free from any kind of violence, is emphasised.